The Hepplemeyer Phenomenon: Subtly Demonstrating the Co-opting of Science into Unscientific Contexts - Pittaway, D. (South African Journal of Higher Education, 2022)
In this article I propose that a short story, in this case Howard Fast’s “The Hoop” (1975), can be used for educational purposes to demonstrate (in a quick and undivisive manner) how science can be co-opted into unscientific contexts. I also show how the story paves the way for brief explorations of three philosophical topic areas relevant in the context of science education, namely Horkheimer’s (2004) operationalism and instrumentalism, Kuhn’s (1977) take on theory choice, and Heidegger’s (1977) technological Enframing. The foregrounding of a short story for the purpose of education within the sustainability sciences is offered as an interim step towards transgressive learning and disruptive capacity-building processes called for elsewhere.